Обслуживание в читальных залах ЦНБ ХНУ им. В.Н. Каразина: креативный подход - Назарова, О.В. (Харків : ХНМУ, 2015)
В статье на примере читального зала периодики ЦНБ ХНУ им. В.Н. Каразина показан новый, креативный подход к обслуживанию читателей, способах их привлечения в библиотеку (тематические ретро-выставки, проведение различных мероприятий), а также рассмотрены результаты опроса читателей (анкета «Качество обслуживания в библиотеке»). У статті на прикладі читального залу періодики ЦНБ ХНУ ім. В. Н. Каразіна розглянуто новий, креативний підхід до обслуговування читачів, способах їх залучення до бібліотеки (тематичні ретро-виставки, проведення різноманітних заходів), а також наведені результати опитування читачів (анкета «Якість обслуговування у бібліотеці»). A new and imaginative approach for users services, methods of users attraction to the library (retro-themed exhibitions, a variety of activities) in the context of periodical reading room of Central Scientific Library of V.N. Karazin Kharkiv National University also presents the results of a survey of readers (form «The amount of services in the library») are regarded in this article.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Book and library history; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Харьковский университет; история библиотек; Kharkov University; Центральная научная библиотека; історія бібліотек; Kharkov National University; library; креативный подход; ретро-выставка; библиотека; креативний підхід; ретро-виставка; бібліотека; imaginative approach; retro-exhibition; Харьковский национальный университет имени В.Н. Каразина